Improvement of flexural properties and dimensional stability of rice husk particleboard using wood strand from (azadirachta excelsa) in face layer / Muhamad Zahir Nazri - Nazri, Muhamad Zahir (Faculty of Applied Sciences, 2017)
Improvement of flexural properties and dimensional stability of rice husk particleboard is targeted in this study. Five ratios of Azadirachta excelsa (0, 10, 20, 30 and 40%) at face layer were tested. Further work was done with 40% Azadirachta excelsa content with random and aligned arrangement. The results showed significant (p ≤ 0.05) improvement in flexural strength (MOR and MOE) as the face layer percentage increases. The dimensional stability (water absorption and thickness swelling) with 40% give the best performance. Arrangement of strength has no significant effect. Overall there is potential to improve the flexural and dimensional stability with variation of strands at face layer.